2021
DOI: 10.1016/j.lanepe.2020.100020
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness, worries, anxiety, and precautionary behaviours in response to the COVID-19 pandemic: A longitudinal analysis of 200,000 Western and Northern Europeans

Abstract: Background In response to the COVID-19 pandemic, governments around the world instituted various public-health measures. Our project aimed to highlight the most significant similarities and differences in key mental-health indicators between four Western and Northern European countries, and identify the population subgroups with the poorest mental-health outcomes during the first months of the pandemic. Methods We analysed time-series survey data of 205,084 individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
214
4
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(246 citation statements)
references
References 34 publications
21
214
4
7
Order By: Relevance
“…A long-term study found a reduction or return to normal levels of anxiety among people in isolation during MERS (Jeong et al, 2016). Studies also have shown reductions in worry (Bendau et al, 2020;Varga et al, 2021) and a slight increase in happiness during the late phase of the COVID-19 lockdown in April 2020 (Stieger et al, 2021). Similarly, a recent study (Bendau et al, 2021) found that COVID-19-related fear, anxiety, and depressive symptoms decreased on average over time (March to June), again showing that most people grow accustomed to challenging new situation over time.…”
Section: Discussionmentioning
confidence: 99%
“…A long-term study found a reduction or return to normal levels of anxiety among people in isolation during MERS (Jeong et al, 2016). Studies also have shown reductions in worry (Bendau et al, 2020;Varga et al, 2021) and a slight increase in happiness during the late phase of the COVID-19 lockdown in April 2020 (Stieger et al, 2021). Similarly, a recent study (Bendau et al, 2021) found that COVID-19-related fear, anxiety, and depressive symptoms decreased on average over time (March to June), again showing that most people grow accustomed to challenging new situation over time.…”
Section: Discussionmentioning
confidence: 99%
“…The increased precautionary behavior uptakes may be also related to the increase of interpersonal contacts (e.g., school reopen) at wave 2, leading to more practices of wearing masks and personal hygiene. Such changes in personal precautionary behaviors have also been documented in an international study, revealing a significant increase of precautionary behaviors after the national governmental intervention among Western and Northern Europeans (Varga et al, 2021 ).…”
Section: Discussionmentioning
confidence: 58%
“…Levels of loneliness, worries, anxiety and precautionary behaviors in response to the pandemic were some of the feelings observed by Varga et al, (2021) in the European population. The risk of falling ill or of someone close to you was reported as one of the biggest concerns of the interviewees.…”
Section: Imagementioning
confidence: 96%